Orientation : and other stories - Orozco, Daniel, 1957- (Faber and Faber, Inc., 2011)
In this collection, Orozco leads the reader through the secret lives and moral philosophies of bridge painters, men housebound by obesity, office temps, and warehouse workers. Each story in the collection has a gut-punch impact, softened only by lyricism and black humor.